Search for high-mass Wγ and Zγ resonances using hadronic W/Z boson decays from 139 fb−1 of pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2023)
A search for high-mass charged and neutral bosons decaying to Wγ and Zγ final states is presented in this paper. The analysis uses a data sample of $$ \sqrt{s} $$= 13 TeV proton-proton collisions with an integrated luminosity of 139 fb−1 collected by the ATLAS detector during LHC Run 2 operation. The sensitivity of the search is determined using models of the production and decay of spin-1 charged bosons and spin-0/2 neutral bosons. The range of resonance masses explored extends from 1.0 TeV to 6.8 TeV. At these high resonance masses, it is beneficial to target the hadronic decays of the W and Z bosons because of their large branching fractions. The decay products of the high-momentum W/Z bosons are strongly collimated and boosted-boson tagging techniques are employed to improve the sensitivity. No evidence of a signal above the Standard Model backgrounds is observed, and upper limits on the production cross-sections of these bosons times their branching fractions to Wγ and Zγ are derived for various boson production models.
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Im Titel ist der Ausdruck "-1" hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.02.2024